Analisis Pemanfaatan Sistem Informasi JKN Mobile Di Kota Makassar - Senja Narmansyah; Indar; Suci Rahmadani; Muhammad Alwy Arifin; Ridwan M Thaha (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
JKN Mobile is an application presented by BPJS Kesehatan to make it easier for users to register, change and find membership data, obtain First Level Health Facility services and Advanced Level Referral Facility and make it easier for users to provide criticism or suggestions. BPJS participants are still lacking in utilizing the JKN Mobile application service, even though the formation of this application is expected to make it easier for the public to access health services from BPJS Kesehatan. This study aims to determine the utilization of the JKN Mobile information system in Makassar City. The type of research used is quantitative research with an analytical survey method and using a cross sectional study design. The population in this study were all BPJS Kesehatan participants in Makassar City who used the JKN Mobile application as many as 245,341 users. Sampling using nonprobability sampling technique by accidental sampling with a total sample of 100 people used. The results showed that 86% of respondents felt that the use of JKN Mobile was sufficient. The results of statistical analysis using Chi Square showed that the system quality (p=0.000), information quality (p=0.000) and service quality (p=0.000). The p-value of all independent variables <0.05 so that there is a relationship between system quality, information quality and service quality on the utilization of JKN Mobile in Makassar City. All variables studied in this study indicate that there is a relationship with the use of JKN Mobile. With this, it is hoped that BPJS Kesehatan will improve and develop the JKN Mobile application, especially on the registration and registration to make it more easily accessible to all groups of people and further increase socialization and education to BPJS participants regarding the procedures for using and the importance of using the JKN Mobile application.